Implementasi pendidikan khas kejogjaan melalui permainan tradisional kelereng di SD Negeri Baciro Yogyakarta - Muhammad Giri Prihandaru; Poppy Indriyanti; Ahmad Heri Setyawan (Trihayu: Jurnal Pendidikan Ke-SD-an, 2026)
Education is not only oriented to academic achievement, but also plays an important role in the formation of character and the preservation of local cultural values according to the concept of the Ki Hadjar Dewantara Education Trikon. This study aims to describe the contribution of the traditional game of marbles as a culture-based learning medium in the implementation of Jogjaan Typical Education (PKJ) at SD Negeri Baciro Yogyakarta. The research uses a qualitative approach with a descriptive method. The research subjects consisted of six students, each representing grades I to VI. Data were collected through non-participant observation of the implementation of marble games in PKJ activities. The results of the study show that playing marbles is able to foster social skills, sportsmanship, honesty, emotional control, concentration, and fine motor skills of students. Thus, the implementation of PKJ through the traditional game of marbles is effective as a means of instilling local cultural values in Yogyakarta contextually without increasing the academic burden of students.